2022
DOI: 10.5465/annals.2020.0330
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Communities of Practice: Taking Stock and Moving Forward

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 301 publications
0
22
0
1
Order By: Relevance
“…Besides, the conventional knowledge of CoPs is being challenged by current discussions on the future of work and new methodological advancements, which also present research opportunities and novel conceptual fusions. It is also highlighted that new theories and conceptualizations may emerge through the interaction of the lenses, the CoP theory, and related literature (Nicolini, Pyrko, Omidvar, & Spanellis, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the conventional knowledge of CoPs is being challenged by current discussions on the future of work and new methodological advancements, which also present research opportunities and novel conceptual fusions. It is also highlighted that new theories and conceptualizations may emerge through the interaction of the lenses, the CoP theory, and related literature (Nicolini, Pyrko, Omidvar, & Spanellis, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Looking forward and acknowledging the value of using specialized knowledge from external sources for pharmaceutical innovation, further insights are needed to accelerate knowledge sharing. Future research in the area of communities of practices (CoP)—defined as communities where members invest their identities in order to learn together and from each other about problems that they genuinely care about (Brown & Duguid, 1991 ; McDermott, 2000 ; Nicolini et al, 2022 ; Pyrko et al, 2017 , 2019 ; Wenger, 1998 )—can be an important area for coping with the open innovation paradox, particularly in areas where academic-practitioner collaboration is useful, such as in the case of OSDD community. We find evidence in our research that managerial biases towards openness, and adoption of ideas ‘not-invented’ within the organization can be important influencing factors for a firm’s open innovation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…loss of physical contact with patients and colleagues reduced opportunities for informal networking and the exchange of information, disrupting shared practice partnerships.Participants had mixed experiences of the organization in terms of well-being support, with the majority of support being shared within professionals' peer and social networks. This mirrors the levels of communities of practice described byNicolini et al (2022) as fluid and heterogeneous, where groups may be supported or structured according to the involvement of the organization. Similarly,Noyes (2022) found that hierarchies of power within clinical environments may create competing pressures in collaborative healthcare groups.…”
mentioning
confidence: 88%